FACTORS THAT INFLUENCE ORAL ANTIDIABETIC DRUG COMPLIANCE IN DIABETES MELLITUS TYPE II PATIENTS IN WORKING AREASMEDICAL IMAGE CLINICS 2 MEDAN CITY IN 2020 - Nur Kholilah Nasution (Jurnal Kajian Kesehatan Masyarakat, 2020)
Diabetes mellitus is a non-communicable disease that will increase in number in the future. According to WHO (2019) the increase in the number of people with Diabetes Mellitus in Indonesia from 8.4 million in 2000 is predicted to be around 21.3 million in 2020. The purpose of the research was to analyze the influence of family support, self motivation, the role of health workers, side effects of drugs, pharmaceutical counseling and the dominant factors with adherence to taking oral antidiabetic drugs in patients with type II diabetes mellitus. The research method uses an observational analytic design with a cross-sectional approach, which was carried out at the Citra Medika 2 Clinic Medan City in January-March 2020 with a total sample of 94 people. The results obtained 37 people (39.4%) adhered to taking medication and 57 people (60.6%) did not comply. There was no influence of family support factors with p (0.405)> α (0.05), self motivation with p (0.424)> α (0.05), pharmaceutical counseling with p (0.371)> α (0.05) on adherence take oral antidiabetic drugs. And there is an influence of the role of health workers with p (0.023)